Questions and Answers Related to the Prebiotic Production of Oligonucleotide Sequences from 3′,5′ Cyclic Nucleotide Precursors - Judit E. Šponer; Jiří Šponer; Aleš Kovařík; Ondrej Šedo; Zbyněk Zdráhal; Giovanna Costanzo; Ernesto Di Mauro (Life, 2021)
Template-free nonenzymatic polymerization of 3′,5′ cyclic nucleotides is an emerging topic of the origin of life research. In the last ten years, a number of papers have been published addressing various aspects of this process. These works evoked a vivid discussion among scientists working in the field of prebiotic chemistry. The aim of the current review is to answer the most frequently raised questions related to the detection and characterization of oligomeric products as well as to the geological context of this chemistry.